Factors influence retirement planning among TNB staffs in Tanah Merah, Kelantan / Norhayumy Basori - Basori, Norhayumy (Bachelor of Business Administration (Hons) Marketing, 2015)
This research was carried out on the respondents at Tenaga Nasional Berhad in Tanah Merah, Kelantan with aim to identify the factors that influencing the TNB staffs for the retirement planning. The purposed of this research study is to investigate the relationship between income level, investment experience, attitude towards money, and levels of financial knowledge among TNB staffs with the retirement planning. This study used the purposive sampling method and the data was obtained through questionnaire distributions. The questionnaire was distributed to the TNB staffs in Tanah Merah, Kelantan and the data was analysed to derive possible findings of the study. The multiple linear regression method was used to measure the relationship between the dependent variable (retirement planning) and independent variables (income level, investment experience, attitude towards money and levels of financial knowledge). The result from the finding shows that the income level and investment experience are significant with the retirement planning, whereas the attitude toward money and levels of financial knowledge are not significant with the retirement planning